THE EFFECT OF FLEXIBILITY WORK ARRANGEMENT THROUGH WORK LIFE BALANCE ON LIFE SATISFACTION - Rinny Dharma Diani; Suparno Suparno; Henry Eryanto; Siti Nurjanah (International Journal Labs, 2024)
This study aims to determine the effect of Work life Balance, Flexible Time Arrangement and Life Satisfaction of Indonesian Ombudsman employees. The research population used was the Ombudsman of the Republic of Indonesia, while the sample used amounted to 102 employees. The sampling technique uses random sampling in employees both at the Indonesian Ombudsman who are at the center and at the representative. Data analysis techniques using Structural Equation Modeling (SEM). The results of this study show that flexibility work arrangement has a positive effect on Life satisfaction, shown by p value 0.000 < 0.05 and positive path coefficient of 0.503 meaning that the higher the flexibility work arrangement, the higher Life satisfaction. Flexibility work arrangement has a positive effect on work life balance, shown by p value 0.000 < 0.05 and positive path coefficient of 0.576 meaning that the higher the flexibility of work arrangement, the higher the work life balance. Work-life balance has a positive effect on Life satisfaction, shown by p value 0.000 < 0.05 and a positive path coefficient of 0.527 meaning that the higher the work life balance, the higher the Life satisfaction. In this study it can also be concluded that Work life balance can mediate the effect of flexibility work arrangement on Life satisfaction, indicated by p value 0.000 < 0.05, based on the value of R square adjusted variable Life satisfaction of 0.833 this means 83.3% of the variable Life satisfaction is influenced by the variables flexibility work arrangement and work life balance, while the remaining 16.7% variable Life satisfaction is influenced by factors outside the variable flexibility work arrangement and work life balance. Furthermore, the variable work life balance shows an R square adjusted of 0.325, this means that 32.5% of the variability of work life balance is influenced by the variable flexibility work arrangement, while the remaining 67.5% of the variable work life balance is influenced by factors other than the variable flexibility work arrangement.